Employee Provident Fund (EPF) office at Seri Manjung / Wan Nur Atikah Wan Ismail - Wan Ismail, Wan Nur Atikah (Universiti Teknologi MARA, Perlis, 2023)
Industrial training is very important for every student because here we experienced real working life. The main objective about this report is able to analysis SWOT of the Employee Provident Fund(EPF). In this report contains seven parts where the first part is preliminary pages. Part two of this report consist of student profile and the next partis company's profile. There are parts about my training reflection such as my experience and task that given to me during industrial training . In this report also, there are SWOT analysis and SWOT Matrix. There are three points for each strength, weakness, opportunities and threats. In discussion part, I do provide some recommendation to improve weaknesses and threats and to strengthen the strength and opportunities.